Online Experimentation Forum - Cardoso, Alberto; Restivo, Maria Teresa; Guerra, Helia M.G.; Gomes, Luis M.P. (International Journal of Online and Biomedical Engineering (iJOE), 2016)
Online experimentation is based on emerging technologies for remote and virtual experimentation also aided and complemented by other online applications based in virtual reality, augmented reality, sensorial devices, potentiated by additional tools like live videos, interactive videos and serious games available through web platforms, which promote user immersion in virtual environments recreating the reality. This Special Issue collects a set of selected short papers describing 22 different works exploring online experimentation, demonstrated during the Exhibition Sessions of the 3rd edition of the Experiment@International Conference – exp.at’15.